Ethanol Alters Production and Secretion of Estrogen-Regulated Growth Factors That Control Prolactin-Secreting Tumors in the Pituitary - Sarkar, Dipak K. (2007)
BACKGROUND: Chronic administration of ethanol increases plasma prolactin levels and enhances estradiol’s mitogenic action on the lactotropes of the pituitary gland. The present study was conducted to determine whether ethanol’s lactotropic cell-proliferating action, like estradiol’s, is associated with alteration in the production of 3 peptides that regulate cell growth: transforming growth factor beta 1 (TGF-β1), TGF-β3 and basic fibroblast growth factor (bFGF). METHODS: Using ovariectomized Fischer-344 female rats, we determined ethanol’s and estradiol’s actions on lactotropic cell proliferation and growth-regulatory peptide production and release in the pituitary gland during tumorigenesis. RESULTS: Ethanol increased basal and estradiol-enhanced mitosis of lactotropes in the pituitary glands of ovariectomized rats. The level of growth-inhibitory TGF-β1 was reduced in the pituitary following ethanol and/or estradiol treatment for 2 and 4 weeks. In contrast, ethanol and estradiol alone as well as together increased levels of growth-stimulatory TGF-β3 and bFGF in the pituitary at 2 and 4 weeks. In primary cultures of pituitary cells, both ethanol and estradiol reduced TGF-β1 release and increased TGF-β3 and bFGF release at 24 hours. Ethanol’s effect on growth factor levels in the pituitary or growth factor release from the pituitary cells was less than that of estradiol. When ethanol and estradiol were applied together, their individual effects on these growth factors were amplified. CONCLUSIONS: These results confirm estradiol’s modulation of pituitary growth factor production and release, and provide evidence that ethanol, like estradiol, alters the production and secretion of growth-regulatory peptides controlling lactotropic cell proliferation.